The contemporary vision of marketing And its impact in crystallizing the chances of success of the new product - علي, نعمة شليبة (Journal of Economics and Administrative Sciences, 2009)
The current research aims at identifying the new marketing directions that in the picture because if the changes and challenges that face the business nowadays, these effect on the future of the new product. The problem of the research concentrate on the new marketing activities and how to make it appropriate between the product and the market's need, and to fulfill the needs and desire of the customer and it's importance for achieving the economical goals of the organization for a long relationship with the customer. The resume of the research is about the impact of nowadays marketing and it's effect on knowing the customer instead of concentrating on the important roll of marketing of the customer in the marketing strategic of the organization and create a psychological forever quality beside the achievement of the economical value and the roll of the product, and to move from the product management to the management of customer's relationship.